Early vaccination of laying hens with the live bivalent Salmonella vaccine AviPro™ Salmonella DUO results in successful vaccine uptake and increased gut colonization - Cawthraw, Shaun A.; Goddard, Adam; Huby, Tom; Ring, Isaac; Chiverton, Louise; Mueller-Doblies, Doris (Frontiers in Microbiology, 2024)
Salmonella Enteritidis and S. Typhimurium are the two most clinically important zoonotic Salmonella serovars and vaccination of breeding and laying hens affords effective Salmonella control. The use of live vaccines has proven beneficial for a number of reasons, including ease of application, protection from the first day of life onwards and initiation of a strong local immune response. Live vaccines can be applied in the drinking water from the first day of life onwards, but some rearers choose to wait until the end of the first week to ensure sufficient water consumption. However, this practice leaves the birds unprotected during the crucial first week of life, where they are most susceptible to colonisation by field strains. The aim of this study was to determine if successful vaccine uptake is achieved when layer pullets are vaccinated as early as day one. Three pullet flocks were vaccinated at 1, 2, 3 or 5 days-of-age with AviPro™ SALMONELLA DUO, a live vaccine containing attenuated strains of S. Enteritidis and S. Typhimurium (Elanco Animal Health). The vaccine was administered via the drinking water following manufacturer's instructions. Two days post-vaccination, 10 birds per flock were culled and caecal and liver samples taken, along with two pools of faeces per flock. Levels of vaccine strains were determined by quantitative and qualitative bacteriology. Vaccine strains were detected in all birds from all age groups indicating successful uptake of the vaccine. Levels of the S. Enteritidis vaccine were higher than levels of the S. Typhimurium vaccine, with the latter frequently only detectable following enrichment. There was an inverse correlation between age and caecal levels of vaccines, with the highest numbers seen in birds vaccinated at 1-day-of-age. Interestingly, S. Enteritidis vaccine strain levels in liver samples were highest when birds were vaccinated at 5 days-of-age. These results show that successful uptake of both vaccine strains was evident in all age groups. The earlier the chicks were vaccinated, the higher the vaccine levels in caecal contents. We therefore recommend vaccination of pullets as early as practicably possible to ensure protection against exposure to field strains.